Prevalence of ABCC3‐1767G/A polymorphism among patients with antiretroviral‐associated hepatotoxicity - HariOm Singh; Sonam Lata; Ranjana Choudhari; Tapan N. Dhole (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Plasma concentrations of antiretrovirals (ARVs) regimens have considerably varied in individuals of human immunodeficiency virus (HIV) because of variations in the expression of drug‐metabolizing and transporter genes. Transporter genes play an important role in the disposition of drugs. Polymorphism in transporter gene (ABCC3) affects the MRP3 expression and varies the treatment outcome. Method We examined the polymorphism of ABCC3‐1767G/A gene in a total of 165 HIV patients (out of 165 HIV patients, 34 were with and 131 were without hepatotoxicity) and 156 healthy individuals using the polymerase chain reaction–restriction fragment length polymorphism method. Results In univariate analysis, we found a decreased prevalence of ABCC3 1767GA, 1767GA+AA genotypes, and 1767A allele in patients with hepatotoxicity as compared to patients without hepatotoxicity (23.5% vs. 28.2% and 23.5% vs. 30.53%; 11.76% vs. 16.41%), while a higher prevalence of 1767AA genotype was observed in HIV patients in comparison with healthy controls (2.3% vs. 1.3%, odds ratio [OR] = 1.71, 95% confidence interval [CI]: 0.23–15.03, p = .89). The frequency of ABCC3‐1767AA genotype was dispersed higher in individuals with early and advanced HIV disease stage in comparison with healthy controls (5.3% vs. 1.3%, OR = 4.73, p = .70; 8.9% vs. 1.3%, OR = 1.89, p = .91). A higher occurrence of ABCC3‐1767AA genotype was found in tobacco using HIV patients without hepatotoxicity compared with nonusers (4.7% vs. 1.1%, OR = 4.28, p = .52). The distribution of ABCC3‐1767GA genotype was higher in nevirapine receiving HIV patients irrespective of their hepatotoxicity status as compared to nonusers (30.4% vs. 9.1%, OR = 3.34, p = .22; 29.4% vs. 16.7%, OR = 1.69, p = .77). In multivariate analysis, HIV patients receiving nevirapine and with hepatotoxicity was found to have a significant risk for severity of hepatotoxicity (OR = 4.56, 95% CI: 1.60–12.99, p = .004). Conclusion ABCC3 1767G/A polymorphism was not significantly associated with susceptibility to ARV‐associated hepatotoxicity, although ABCC3 1767AA genotype designated a risk for acquisition of hepatotoxicity and advancement of the disease. Nevirapine usage emerged as an independent risk factor for hepatotoxicity severity.